2017
DOI: 10.1111/ijpp.12387
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self-medication in Spain: a cross-sectional study in different age groups

Abstract: When our data are compared to those from previous Spanish surveys carried out in 2003 and 2006, we can conclude that self-medication is increasing in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 29 publications
0
26
1
3
Order By: Relevance
“…The difference in methodology, especially the definition of self-treatment and self-medication, might account for the deviation in values to some extent. The differences in the contents of self-treatment/self- Utilization of family practice service *P < 0.05; **P < 0.01 medication, as well as the diversity of the period of time considered, would result in the differences in the estimation of the prevalence [9,37].…”
Section: Prevalence Of Self-treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The difference in methodology, especially the definition of self-treatment and self-medication, might account for the deviation in values to some extent. The differences in the contents of self-treatment/self- Utilization of family practice service *P < 0.05; **P < 0.01 medication, as well as the diversity of the period of time considered, would result in the differences in the estimation of the prevalence [9,37].…”
Section: Prevalence Of Self-treatmentmentioning
confidence: 99%
“…The utilisation of family practice services is strongly associated with the lower possibility of self-treatment in the adjusted model. A cross-sectional study in Spain indicated that visits to the family doctor or other specialists in the last 4 weeks are negatively related to selftreatment, especially in the age group of 45-74 years [37]. It was indicated in a study in China that residents who availed of family practice services perceive higher quality of primary care, including the aspect of first contact-access, continuity, comprehensiveness and coordination [18].…”
Section: Predictors Of the Whole Sample Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, several studies suggest that the costs of treatment rise as people get older (3,6). Previous studies show complications of self-medication among elderlies can cause even more harms than good; therefore, it seems to be fundamental to identify such underlying behaviors and try to modify them so that the elderlies can have a long and healthy life (7).…”
Section: Introductionmentioning
confidence: 99%